2018
DOI: 10.1111/edt.12397
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cathepsin K inhibitor surface treatment on delayed tooth replantation in dogs

Abstract: Cathepsin K inhibitor did not demonstrate significant inhibitory effects on root resorption after delayed replantation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Furthermore, several substances have been used for the treatment of the root surface of replanted teeth to increase their retention rate, namely, formol, acid solutions (such as citric acid, hydrochloric acid, acidulated fluoride, and neutral fluoride), alkaline substances (such as calcium hydroxide and NaOCl), antibiotics (such as tetracycline and rifocin), antibiotic/corticosteroid combination, corticosteroid, alendronate, Vitamin C, carbonic anhydrase inhibitor (acetazolamide), Cathepsin K, propolis, and Emdogain (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several substances have been used for the treatment of the root surface of replanted teeth to increase their retention rate, namely, formol, acid solutions (such as citric acid, hydrochloric acid, acidulated fluoride, and neutral fluoride), alkaline substances (such as calcium hydroxide and NaOCl), antibiotics (such as tetracycline and rifocin), antibiotic/corticosteroid combination, corticosteroid, alendronate, Vitamin C, carbonic anhydrase inhibitor (acetazolamide), Cathepsin K, propolis, and Emdogain (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to facilitate greater pulp and periodontal healing, and greater lifetime of the replanted teeth. Thymosin alpha 1, enamel matrix derivative, fibroblast growth factor, triamcinolone, bisphosphonates dexamethasone, 3Mix (the mixture of ciprofloxacin, metronidazole, and minocycline), Cathepsin K inhibitor and fluoride are medicines tried in different models to provide short-term and long-term benefits in the replantation of avulsed teeth [ 13 22 ]. They might exert their beneficial effect on replanted teeth by inhibiting the activity of osteoclasts, controlling the inflammation through decreased C-reactive protein, or favoring the formation of new periodontal ligament.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts are found in several stages of root resorption and cathepsin K is one of the key markers of osteoclastic activity. Previous studies suggested that inhibition of cathepsin K downregulated IL-1, IL-17, and TNFα expression via the RANKL pathway on delayed tooth replantation in dog models 39.…”
mentioning
confidence: 95%